The effect of rebound jumps exercises on the development of some physiological variables and the skill of correcting handball among young players - MOHAMMED JASMAL.EZZI, AZHAR (International Journal of Psychosocial Rehabilitation, 2020)
The research included four chapters. The first chapter contained the introduction to the research and its importance. It was touched upon that the foundations that must be met for the success of the training process in general and handball in particular are focused on developing training exercises based on scientific foundations that work on developing the physiological indicators. Back jump exercises are one of the most important elements. The special physical numbers of the players contribute effectively and decisively with the rest of the other elements to the success and improvement of the level of the handball player in terms of physiological variables. As for the research problem, I noticed there was a fluctuation in the level of correction performance and its various types. Between positive and negative , and the back of humiliation as evident through the failed attempts to straighten , making attention to resolving this problem and aim of the research to Identify the extent of the impact of exercises Olathe P leaps backlash for the skill of shooting in handball dually sample (14) player has conducted tribal posteriori tests and proposed exercises for the sample to get the results and concluded researcher that the adoption of the exercises jumps regressive in working on the development of pulse rate and (Vo2max) and the players' shooting skills in handball. The researcher recommended the adoption of back jump exercises for young players.